2015
DOI: 10.1007/s11325-015-1128-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes from intermittent hypoxia-exposed rats increase the apoptotic signals in endothelial cells via oxidative and inflammatory injury in vitro

Abstract: Lymphocytes from intermittent hypoxia-exposed rats increased the apoptotic signals in endothelial cells via oxidative and inflammatory injury in vitro, which could be attenuated by tempol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Tempol, known as an antioxidant, promotes the clearance of ROS and protects mitochondria from oxidative damage. Previous reports have shown that tempol or other antioxidants can prevent HIF-1α-mediated cancer progression [ 37 , 51 53 ]. Consistent with these reports, our findings suggest that antioxidant tempol attenuated melanoma lung metastasis and oxidative stress, as well as decreased HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tempol, known as an antioxidant, promotes the clearance of ROS and protects mitochondria from oxidative damage. Previous reports have shown that tempol or other antioxidants can prevent HIF-1α-mediated cancer progression [ 37 , 51 53 ]. Consistent with these reports, our findings suggest that antioxidant tempol attenuated melanoma lung metastasis and oxidative stress, as well as decreased HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…It also exerts neuroprotective effects by reducing superoxide anions and preventing peroxynitrite-associated inflammation [ 34 36 ]. Recently, tempol has been confirmed to attenuate apoptotic signals in endothelial cells from IH-exposed rats by decreasing oxidative stress and inflammation injury [ 37 ]. Therefore, it is reasonable to hypothesize that tempol may attenuate IH-induced tumor metastasis by decreasing oxidative stress and inflammation responses.…”
Section: Introductionmentioning
confidence: 99%
“… 40 Tempol was also found to attenuate the pro-apoptotic effect of IH-induced lymphocytes on endothelial cells. 26 We also demonstrated a significant decrease in the apoptosis level of endothelial cells and adhesion molecule levels in OS rats treated with tempol. These results may support the potential of tempol as a treatment for OS-induced cardiovascular complications as an alternative to CPAP.…”
Section: Discussionmentioning
confidence: 50%
“…As previously described, 26 we used a gas control delivery system for IH exposure, which regulated flow (5 L/min) of pure nitrogen or clean air continuously into a customized IH housing chamber (23×20×12 cm=5520 cm 3 ≈5.5 L) to maintain designated continuous hypoxia or normoxia environment. Software edited with Visual C++ computer language (Jing Feng, Tianjin Medical University General Hospital Respiratory Simulation System 1.0, Tianjin, China, 2005) was applied to control the duration of hypoxia (first 30 s) or reoxygenation (latter 90 s) phases, producing 30 cycles of alternations per hour.…”
Section: Methodsmentioning
confidence: 99%
“…Then, in turn, the stabilization of HIF-1α promotes the synthesis of ROS in mitochondria to induce cell death via the suppression of AMP-activated protein kinase (100,101). HIF-1α stabilization, along with a decline in Bcl-2 and substantial caspase-3 expression, has been observed after IH exposure (102). Furthermore, a large number of apoptotic events have been identified in rat myocardium exposed to IH (103), and the inhibition of HIF-1α expression has been shown to decrease neuronal apoptosis (104).…”
Section: Ros-induced Consequences Lead To Cognitive Impairment In Slementioning
confidence: 99%